Scintigraphy in Thyroid Nodular Pathology - S. P. Mironov; V. B. Sergienko (Вестник рентгенологии и радиологии)
Thyroid scintigraphy is a method that formed more than 60 years ago and retains its importance for the diagnosis and assessment of the risk of nodular malignancy. The review examines the use of the scintigraphic method in functional and metabolic assessment of nodular goiter. Prerequisites for functional thyroid nodes screening with short-lived 99mTc-pertechnetate are outlined. Information is provided on the principles of its preparation and pharmacokinetics, as well as variants of the thyroid nodes functional activity, their possible malignant potential and indications for metabolic screening. The characteristic of metabolic activity allows to assess the risk of functionally “cold” thyroid nodes malignancy. The main stages of the use of nonspecific tumorotropic radiopharmaceuticals, the mechanism of their accumulation and metabolism in the thyroid tumors, the possibilities of the differential diagnosis of various types of nodular formations are presented. Modern views on the diagnostic capabilities of two-phase scintigraphy with 99mTс-methylisobutylisonitrile are reflected taking into account the relationship of radiopharmaceuticals accumulation with factors of proliferative activity and ultrastructural cell types, a variant of oncocytic pathology and multidrug-resistant protein expression.